1986
DOI: 10.1530/jrf.0.0770569
|View full text |Cite
|
Sign up to set email alerts
|

Plasma prolactin concentrations and cyclic activity in pony mares during parturition and early lactation

Abstract: Five pony mares were blood sampled during late pregnancy, foaling and early lactation. An homologous assay for horse prolactin was used to measure plasma prolactin concentrations in these samples. Regular estimates of cyclic activity were also made. Plasma prolactin concentrations rose markedly in the last week of pregnancy and remained high although variable in early lactation, before declining to basal levels by 1-2 months post partum. All mares showed a post-partum oestrus 7.0 +/- 0.9 days after parturition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 16 publications
3
14
0
1
Order By: Relevance
“…In our present study, plasma PRL concentrations also increased during treatment and returned to the basal level immediately after the end of treatment, but the mare still produced a sufficient amount of milk and was able to raise the foal until weaning, just as typical parturient mares do. This result supports the hypothesis of previous studies [15,32], which states that the sudden increase in plasma PRL concentrations as shown in healthy gestation could be the trigger for the onset of lactation.…”
Section: Discussionsupporting
confidence: 92%
“…In our present study, plasma PRL concentrations also increased during treatment and returned to the basal level immediately after the end of treatment, but the mare still produced a sufficient amount of milk and was able to raise the foal until weaning, just as typical parturient mares do. This result supports the hypothesis of previous studies [15,32], which states that the sudden increase in plasma PRL concentrations as shown in healthy gestation could be the trigger for the onset of lactation.…”
Section: Discussionsupporting
confidence: 92%
“…Assim Knuiman et al 45 , com humanos, e Watson, Packard e Shepherd 41 com éguas, verificaram que a concentração de colesterol plasmático é significativamente relacionada com triglicerídeos. Na lactação, de acordo com Worthy et al 46 , o teor de colesterol permanece alto, e a concentração de ácidos graxos aumenta significativamente. Ao investigarem em ratos, o tempo decorrido da lipemia pós-prandial, quando esses receberam manteiga, óleo de palmeira, de milho e de canola ou azeite, Lay e Ney 47 constaram que aqueles que receberam gordura mais saturada mostraram maior concentração de colesterol e, portanto maior lipedemia pós-prandial.…”
Section: Resultsunclassified
“…Although equine GH (eGH) has been purified (Saxena and Henneman, 1966; Hartree et al, 1968;Conde et al, 1973) and antisera have been raised in rabbits (Poskus ef al, 1976) inadequate supplies of the hormone have precluded the development of a homologous radioimmunoassay (RIA) for its measurement. A role for eGH in the anabolic process of foal growth is presumed and a galactopoietic role similar to that in ruminants has been suggested (Worthy et al, 1986). The purification of equine PRL (ePRL) has been previously described (Chen et al, 1979;Li and Chung, 1983) and there are several RIAs available for its measurement (Roser et al, 1984;Johnson, 1986; Thompson et al, 1986a;Worthy et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The purification of equine PRL (ePRL) has been previously described (Chen et al, 1979;Li and Chung, 1983) and there are several RIAs available for its measurement (Roser et al, 1984;Johnson, 1986; Thompson et al, 1986a;Worthy et al, 1986). Prolactin is likely to control the growth and function of the mammary gland during a normal gestation and lactation (Worthy et al, 1986) and may also be involved in ovarian function in the mare (Roser et al, 1987). It has also been suggested that PRL may be involved in infertility post partum (Worthy et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation